2016
DOI: 10.1371/journal.pone.0151183
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Biochemical Characterization of Alvinella pompejana Cys-Loop Receptor Homologues

Abstract: Cys-loop receptors are membrane spanning ligand-gated ion channels involved in fast excitatory and inhibitory neurotransmission. Three-dimensional structures of these ion channels, determined by X-ray crystallography or electron microscopy, have revealed valuable information regarding the molecular mechanisms underlying ligand recognition, channel gating and ion conductance. To extend and validate the current insights, we here present promising candidates for further structural studies. We report the biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…The naming convention was subsequently adopted such that by definition the α subunits are those with the vicinal SS. Indeed it has remained true that all functional pentamers in nAChR, and in many similar receptors across a wide variety of organisms, contain at least one α subunit which forms the “principal” face of the intersubunit binding site 40-42 , opposite the “complementary” binding face of the adjacent subunit. [Note: the vicinal SS is in “Loop C”, not in the 13-residue “Cys loop” that is also an important feature of the principal binding face.…”
Section: Resultsmentioning
confidence: 99%
“…The naming convention was subsequently adopted such that by definition the α subunits are those with the vicinal SS. Indeed it has remained true that all functional pentamers in nAChR, and in many similar receptors across a wide variety of organisms, contain at least one α subunit which forms the “principal” face of the intersubunit binding site 40-42 , opposite the “complementary” binding face of the adjacent subunit. [Note: the vicinal SS is in “Loop C”, not in the 13-residue “Cys loop” that is also an important feature of the principal binding face.…”
Section: Resultsmentioning
confidence: 99%
“…We further refer to this structure as Alpo4 CHAPS . CHAPS was present in the purified Alpo4 at a concentration of 0.007% (110 μM) because of its thermostabilizing effect on Alpo4 26 . At 110 μM, the CHAPS concentration is 70-fold lower than the critical micellar concentration (CMC) of the detergent, suggesting a specific interaction with Alpo4 beyond modulating properties of the detergent belt and therefore is consistent with CHAPS binding to the orthosteric site 31 .…”
Section: Resultsmentioning
confidence: 99%
“…The high biochemical stability and preliminary characterization using negative stain electron microscopy suggested that Alpo4 was a promising target for structural studies 27 . However, despite exhaustive screening in different expression systems in combination with a compound library, including acetylcholine and serotonin, we could not identify the agonist/neurotransmitter for Alpo4, thereby limiting functional studies 26 . Because of its biochemical stability and unique position between nAChRs and 5-HT 3 receptors we characterized the structure of Alpo4 using single-particle electron cryogenic microscopy (cryo-EM).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…As the mammalian ligand appeared later in evolution, we could draw up a scenario in which an ancestral ligand, phylogenetically unrelated to the human one, but very similar to it in its binding properties, was replaced in some branches, including the mammals [32]. Such scenarios have already been described [33,34]. Indeed, thanks to these examples, we understand that for these partners, the receptor in fact did not appeare before its first ligand.…”
Section: Plos Onementioning
confidence: 94%